2021
DOI: 10.1088/1748-0221/16/12/c12001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of shutdown dose rates in the ITER Collective Thomson Scattering system and in equatorial port plug 12

Abstract: The ITER Collective Thomson Scattering (CTS) system will be the main diagnostic responsible for measuring the velocity distribution function of fusion-born alpha particles in the plasma. As the CTS diagnostic is integrated in the equatorial port plug 12 (drawer 3), with direct apertures to the port interspace where maintenance hands-on operation will be carried out, it is essential to assess the shutdown dose rates (SDDR) in these maintenance areas. In this work, the D1S-UNED3.1.4 Monte-Carlo transport code, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The analysis also confirmed that the present design of the CTS system remains compliant with the radiation safety requirements, and that from the neutronics point of view, no further design optimization of the CTS system is needed 43 .…”
Section: Please Cite This Article As Doi:101063/50101867supporting
confidence: 73%
See 1 more Smart Citation
“…The analysis also confirmed that the present design of the CTS system remains compliant with the radiation safety requirements, and that from the neutronics point of view, no further design optimization of the CTS system is needed 43 .…”
Section: Please Cite This Article As Doi:101063/50101867supporting
confidence: 73%
“…and apertures for the components and the microwave beams) has closely accompanied the development of the design. The purpose has been to determine if modifications done for diagnostic performance reasons would violate the requirements on the shutdown dose rates (SDDR) at the equatorial port plug closure plate in the port interspace for hand-on maintenance purpose [41][42][43] . By requirement, the dose level in the ports cells, where hands-on maintenance is planned, should not exceed 100 μSv/h 10 6 seconds (~12 days) after shutdown.…”
Section: Please Cite This Article As Doi:101063/50101867mentioning
confidence: 99%
“…As mentioned before, there are no limits defined for the neutron and gamma fluxes in the DEMO port cell, and no calculations of shutdown dose rates are provided here. However, it seems feasible, based on the simulation experience from ITER (although the dose rates will depend on the components present in the port cell and on the integrated fluxes) [62], to comply with the limit of 100 µSv/h in the port cell 12 days after shutdown with neutron fluxes below 1 × 10 8 n cm −2 s −1 reaching the port cell. Nevertheless, shutdown dose rate simulations with models of the port cell components are required to assess the compliance with the limit.…”
Section: Alternative Configuration Of the X-ray Spectroscopy Diagnosticmentioning
confidence: 99%